1999
DOI: 10.1021/jp991106n
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Investigation of Fe−N−O Structure of Nitrosylheme in Myoglobin and Its Mutants

Abstract: Resonance Raman spectra have been observed for NO adducts of wild-type (WT) sperm whale myoglobin (MbNO) and its H64G, H64L, L29W, V68W, and V68T mutants at neutral and acidic pH. Raman excitation in resonance with the Soret band enabled us to detect the Fe−NO stretching (νFe - NO), N−O stretching (νNO), and Fe−N−O bending (δFeNO) bands. The νFe - NO, δFeNO, and νNO bands of WT MbNO at neutral pH were observed at 560, 452, and 1613 cm-1, respectively, and substitution of the distal His64 to Gly or Leu caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
98
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 74 publications
26
98
1
Order By: Relevance
“…However, the bands at 497 and 496 cm Ϫ1 were assigned to ␦(Fe-N-O) bending rather (Fe-NO) stretching (31) on the basis of IR studies of metal nitrosyl complexes, which indicated larger 15 NO isotope shifts for ␦(M-N-O) modes (6-15 cm Ϫ1 ) than for (M-NO) modes (1-6 cm Ϫ1 ) (38,39). Subsequent resonance Raman studies of nitrosyl hemes (19)(20)(21) have clearly shown that these ranges are applicable only to near-linear MNO units. Moreover, the pattern of isotope shifts observed for the 497 and 496 cm Ϫ1 bands in these complexes, i.e., larger isotope shift for 15 NO than N 18 O (31), is a characteristic of the (M-NO) modes of bent FeNO units in nitrosyl hemes (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the bands at 497 and 496 cm Ϫ1 were assigned to ␦(Fe-N-O) bending rather (Fe-NO) stretching (31) on the basis of IR studies of metal nitrosyl complexes, which indicated larger 15 NO isotope shifts for ␦(M-N-O) modes (6-15 cm Ϫ1 ) than for (M-NO) modes (1-6 cm Ϫ1 ) (38,39). Subsequent resonance Raman studies of nitrosyl hemes (19)(20)(21) have clearly shown that these ranges are applicable only to near-linear MNO units. Moreover, the pattern of isotope shifts observed for the 497 and 496 cm Ϫ1 bands in these complexes, i.e., larger isotope shift for 15 NO than N 18 O (31), is a characteristic of the (M-NO) modes of bent FeNO units in nitrosyl hemes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Six-coordinate S ϭ 1͞2 {FeNO} 7 species in heme proteins have much stronger Fe-NO bonds, as evidenced by (Fe-NO) frequencies in the range 536-558 cm Ϫ1 (20,21,41), and much weaker N-O bonds, as evidenced by (N-O) frequencies in the range 1,555-1,624 cm Ϫ1 (20,21). Although no clear consensus has emerged concerning the most appropriate description of the electronic structure and bonding in S ϭ 1͞2 {FeNO} 7 species (18,32,42), the increase in Fe-NO bond strength and concomitant decrease in the N-O bond strength, compared with S ϭ 3͞2 {FeNO} 7 species, appear to be a direct consequence of increased -donation into the empty d z2 orbital that results from lowering the Fe spin state from high to low or intermediate spin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Tomita et al (19) and Vogel et al (20) performed resonance Raman studies on ferrous NO adducts of myoglobin and heme model compounds and showed that the vibrational properties of the Fe-NO unit are distinctly different from those of the Fe-CO unit. For the CO ligand, the two main factors that affect the Fe-CO and C-O frequencies are: 1) the polarity of distal residues in the heme pocket and their proximity to the CO, and 2) the nature of the axial ligand trans to the CO (16,17,21,22).…”
mentioning
confidence: 99%